PERAN CORPORATE SOCIAL RESPONSIBILTY DAN INTELLECTUAL CAPITAL TERHADAP REPUTASI DAN KINERJA KEUANGAN PERUSAHAAN - Candradewi, Made Reina; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p07, 2024)
This research aims to analyze the influence of corporate social responsibility (CSR) and intellectual capital on the reputation and financial performance of companies in the Indonesian capital market, namely manufacturing companies listed on the Indonesia Stock Exchange (BEI). It is hoped that this research will provide insight into companies to create a company reputation and improve financial performance by paying attention to the implementation of CSR and good management of intellectual capital. Apart from that, it is hoped that this research will enrich the body of knowledge regarding the relationship between CSR, intellectual capital, company reputation and financial performance. This research was conducted using a quantitative approach. The sampling technique used in this research is the purposive sampling method. The companies included in this research sample are manufacturing companies that were always listed on the IDX from 2018 to 2021, published financial reports and were registered on IMACAWARD, so the final sample totaled 32 companies. Based on the results of regression analysis and mediation tests, it can be concluded that the CSR variable has a significant positive effect on Company Reputation. The Intellectual Capital variable does not have a significant effect on company reputation. Apart from that, the variables CSR and Company Reputation were found to have no significant effect on the company's financial performance. However, Intellectual Capital was found to have a significant positive effect on Company Financial Performance. The Company Reputation variable was found unable to mediate the relationship between CSR and Intellectual Capital on Financial Performance.